Efektivitas Struktur Bahasa Inggris terhadap Pemahaman Bahasa Penyandang Disabilitas Pendengaran - sunarwanaisyah; Trisna Dinillah Harya; Solihin Solihin; Diana Ambarwati (JPI (Jurnal Pendidikan Inklusi), 2026)
The primary challenge faced by individuals with hearing impairments lies in the process of communication with hearing individuals, particularly because sign language possesses grammatical rules and structural systems that differ significantly from both spoken and written languages, including Indonesian and English. These differences affect their ability to comprehend and construct linguistic structures in written form. This study aims to analyze the role of English language structure in shaping language comprehension among individuals with hearing impairments. This research employs a qualitative approach using a critical ethnographic method involving 12 deaf participants. Data were collected through in-depth interviews, participant observation, and documentation of written interactions via digital media (WhatsApp). The data were analyzed thematically, with a focus on patterns of language use and sentence structure. The findings indicate that limited access to spoken language results in restricted vocabulary among participants, leading to less systematic sentence construction. Furthermore, sign language does not fully conform to the structural rules of verbal languages, which creates challenges in transferring meaning into written form. Specifically, 83% of participants demonstrated better comprehension of simple English structures compared to the more complex and affix-rich structures of Indonesian. This can be attributed to the relatively simpler grammatical patterns of English, which are more easily processed visually. The practical implications of this study highlight the need for adaptive language learning strategies for individuals with hearing impairments. These strategies should emphasize simplified structures, visual-based instruction, and bilingual approaches that take into account the unique characteristics of sign language.